Increased Autonomous Bioluminescence Emission from Mammalian Cells by Enhanced Cofactor Synthesis - Theresa Brinker; Carola Gregor (Chemosensors)
The bacterial bioluminescence system has been successfully implemented in mammalian cell lines, enabling the substrate-free luminescence imaging of living cells. One of the major limitations of the system is its comparatively low brightness. To improve light emission, we aimed to increase the cellular production of FMNH2 and NADPH, which serve as cosubstrates in the bacterial bioluminescence reaction. We coexpressed different proteins involved in the synthesis of these two cofactors together with the proteins of the bacterial bioluminescence system in different mammalian cell lines. The combined expression of a riboflavin kinase (RFK) and a constitutively active Akt2 variant (Akt2CA) that participate in the cellular production of FMN and NADP+, respectively, increased bioluminescence emission up to 2.4-fold. The improved brightness allows autonomous bioluminescence imaging of mammalian cells at a higher signal-to-noise ratio and enhanced spatiotemporal resolution.